Long‐term clinical and angiographic outcomes of percutanenous coronary intervention with everolimus‐eluting stents for the treatment of cardiac allograft vasculopathy. Issue 1 (10th November 2016) - Cheng, Richard; Vanichsarn, Christopher; Patel, Jignesh K.; Currier, Jesse; Chang, David H.; Kittleson, Michelle M.; Makkar, Raj; Kobashigawa, Jon A.; Azarbal, Babak
Abstract : Background: Percutaneous coronary intervention (PCI) with bare‐metal and first‐generation drug‐eluting stents (DES) for cardiac allograft vasculopathy (CAV) is associated with unexpectedly high restenosis rates and target lesion revascularization (TLR). Long‐term outcomes of stenting for CAV using second‐generation everolimus‐eluting stents (EES) are not established. Objective: To evaluate clinical and angiographic outcomes of CAV stenting with EES. Methods: Patients who underwent PCI with EES for CAV were studied. Surveillance angiography was performed at 6–12 months post‐PCI and as indicated. Patient survival, freedom from MACE, binary restenosis, TLR, target vessel revascularization (TVR), and non‐TVR are reported. Results: One‐hundred and thirty two EES were placed in 113 discrete lesions in 48 patients. Pre‐PCI stenosis was 82.1 ± 12.4%, and average stent length and diameter were 16.9 ± 5.7 and 3.0 ± 0.6 mm, respectively. Mean follow‐up was 30.7 ± 18.8 months. Time from transplantation to PCI was 9.9 ± 5.1 years. Post‐PCI survival at 1 (93.5 ± 3.6%), 2 (91.0 ± 4.3%), and 3 years (83.8 ± 6.3%), and freedom from MACE (87.2 ± 4.9%, 82.3 ± 5.7%, 75.8 ± 6.9%) were high. Binary restenosis at 1 (3.0 ± 1.7%), 2 (6.9 ± 3.2%), and 3 years (10.0 ± 4.3%) mirrored expected rates with EES use in native CAD. One‐, two‐, and three‐year rates of TLR (5.1 ± 2.5%, 14.3 ± 4.6%, and 21.2 ± 6.3%), TVR (17.1 ± 4.5%, 39.0 ± 6.9%, and 46.2 ± 7.8%), and NTVR (26.3 ± 5.4%, 55.4 ± 7.0%, and 58.0 ± 7.0%) remain high. Diabetes was associated with an increased hazard ratio for binary restenosis 6.084 (95% CI 1.271–29.133, P  = 0.024). Conclusions: PCI strategy using EES in the treatment of CAV was associated with a low binary restenosis rate, a high survival rate, and a high rate of freedom from MACE. However, at 3 years, TLR and TVR rates appeared similar to rates observed with first‐generation DES. © 2016 Wiley Periodicals, Inc.